BlaTEM-positive Salmonella enterica serovars Agona and Derby are prevalent among food-producing animals in Chongqing, China - Lai, Jiacui; Mu, Hao; Zhou, Bingqian; He, Jiawei; Cheng, Xiangning; Gan, Yujie; Zhao, Meiyuan; Xie, Mengqi; Zhang, Yang; He, Ying; Yang, Yujiao; Wang, Jian; et al. (Frontiers in Microbiology, 2023)
Salmonella is one of the most important zoonotic pathogens, causing morbidity and mortality in humans and animals. Due to the extensive use of antimicrobials in food-producing animals, the antimicrobial resistance of Salmonella has attracted increasing attention globally. However, few studies on Salmonella from food-producing animals have been reported in Chongqing municipality, China. The aim of the present study was to determine the prevalence, serovar diversity, sequence types, and antimicrobial resistance of Salmonella isolated from livestock and poultry in Chongqing. Meanwhile, we also want to know the presence of β-lactamase genes, plasmid-mediated quinolone resistance (PMQR) genes and quinolone resistance-determining region (QRDR) mutations of Salmonella isolates. A total of 129 Salmonella strains were recovered from 2500 fecal samples at 41 farms from pigs, goats, beef cattle, rabbits, chickens, and ducks. Fourteen serovars were identified, with S. Agona and S. Derby being the dominant serovars. The 129 isolates had high resistance to doxycycline (87.6%), ampicillin (80.6%), tetracycline (79.8%), trimethoprim (77.5%), florfenicol (76.7%) , but were susceptible to cefepime. A total of 114 (88.4%) isolates showed multidrug resistant phenotypes. The prevalence of β-lactamase genes in Salmonella isolates was 89.9% (116/129), and among these isolates, 107 (82.9%) harbored blaTEM, followed by blaOXA (26, 20.2%), blaCTX-M (8, 6.2%), and blaCMY (3, 2.3%). In addition, qnrB, qnrD, qnrS, oqxA, oqxB, and aac(6')-Ib-cr were detected in 11, 2, 34, 34, 43, and 72 PMQR-producing isolates, respectively. Moreover, QRDR mutations were very common in PMQR-positive Salmonella isolates (97.2%, 70/72) with mutation(s) in parC or combinative mutations in gyrA and parC. More significantly, 32 extended spectrum beta-lactamase (ESBL)-producing isolates were identified, and 62.5% of them were found to harbor one to four PMQR genes. Furthermore, 11 sequence types were identified from the isolates, and most of ESBL-producing isolates were attributed to ST34 (15.6%) and ST40 (62.5%). The coexistence of PMQR genes with β-lactamase genes and the extensive mutations in QRDR present in Salmonella isolates from food-producing animals suggest a potential threat to public health. Reasonable utilization and strict control strategies for antimicrobials in animal husbandry and animal treatment are necessary to reduce the emergence and dissemination of drug-resistant Salmonella isolates.